Analisis Personal PUMIK (Perempuan Pengusaha Mikro) di Surabaya dalam Upaya Pengembangan Keberhasilan Usaha Bidang Ritel yang Dimoderasi Faktor Kultural - Ardhanari, Margaretha (Jurnal Widya Manajemen & Akuntansi, 2007)
Nowadays, the existency of small, medium micro enterprises is becoming the economic life reality in Indonesia. The women's role in micro enterprises are expected be a 'gate keeper' of economic society. As can be seen from statistic bureau, 44.29% micro enterprises and 10.28% small enterprises are owed by women, respectively. However, women entrepreneur face more complex problems regarding personal characteristic in aims to growth optimally. Moreover, the multi roles of women enterprises are related to the personal. Personal factors are defined by position and status domestically. Both of them can be constraints of women entrepreneur. This research draws several aims. Firstly, the influence of personal factor of multi role of to the succed of retail enterprises in Surabaya. Secondly, to understand influence of cultural factors as a moderator of the relationship between personal factor of multi role and the succed of retail enterprises in Surabaya.